If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -10 = 6x + 3 Reorder the terms: -10 + 15x = 6x + 3 Reorder the terms: -10 + 15x = 3 + 6x Solving -10 + 15x = 3 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -10 + 15x + -6x = 3 + 6x + -6x Combine like terms: 15x + -6x = 9x -10 + 9x = 3 + 6x + -6x Combine like terms: 6x + -6x = 0 -10 + 9x = 3 + 0 -10 + 9x = 3 Add '10' to each side of the equation. -10 + 10 + 9x = 3 + 10 Combine like terms: -10 + 10 = 0 0 + 9x = 3 + 10 9x = 3 + 10 Combine like terms: 3 + 10 = 13 9x = 13 Divide each side by '9'. x = 1.444444444 Simplifying x = 1.444444444
| 13x+8y=11 | | 3x+13=85-5x | | (4n^2-2n)x^2n-2=0 | | 5x+36=12x-52 | | 133-7x=38x+23 | | 9-9x=69-23x | | -72-7x=9x+244 | | 25x^4+10x^2-8x+1=0 | | 6x+152=16x-8 | | 77-3x=3x+5 | | 5x+29=14x-70 | | 75356+25*2y+x*7x=6580*2583x-7y | | 2/5*7-48378322= | | 4y^2+16y=48 | | 4t+2=2t+8 | | (2x+3)(x+5)=(x-3)2 | | 6(15+x)=18x | | -3x-2x=25 | | 7x-6x=11 | | 4(x+2)=2 | | 5x+(4*6)= | | 4p+3q=44 | | 77=10x-3 | | 9n-6=21 | | (2x+3)(2x^2-5x-3)=0 | | 3b=-51 | | 1+5=3 | | 3y^2-27=0 | | 4y^2-1=0 | | 4x-7x-6=0 | | 5+4=5x | | (x+1)+2x=(x-3)(x+3) |